3D chemometric model simulating the Acitheca polymorpha frond: implications for reconstructing carboniferous ferns (Marattiales, Canada) - D`angelo, José Alejandro (2021)
Reported are results of an initial approximate imitation of a Carboniferous fern frond, i.e., marattialean Acitheca polymorpha (Schimper), Middle Pennsylvanian Sydney Coalfield, Canada. The simulation experiment is based on the analysis of 14 infrared spectra obtained by means of Fourier Transform Infrared spectroscopy from four detached fragments of sterile polymorphic penultimate-pinna compressions. The calculated relative, semi-quantitative, chemical data from the infrared spectra are the input for principal component analysis deriving a 3D (three-dimensional) chemometric model. To interpret it, the four specimens are placed in hypothetical-frond positions simulating a tripinnate frond, based on diminishing penultimate-rachial widths from 1-mm (distal) to 10-mm (proximal). Hypothetical conclusions include position-dependent chemistries, specifically that of opposing trends of aromaticity vs. aliphaticity in pinnules-rachises. This, in turn, would suggest potential for (i) fern-frond reconstruction, and (ii) for determination of a most likely frond position of fragmentary specimens by “chemical classification”; the predictive aspect. However, further experimental refinement is necessary particularly based on larger frond segments to confirm or disconfirm the overall hypothetical results.